CREATIVE INDUSTRY REGULATION IN TIMES OF CRISIS: LESSONS FROM COVID-19 ENFORCEMENT AND HEALTHCARE CARTEL POLICIES ACROSS INDIA, AUSTRALIA, AND SINGAPORE - Rai, Kshitij Kumar; Mohammad, Shoaib; Mishra, Satish Kumar; Sharma, Arti; Prajapati, Ramesh; Kumar, Rajiv (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Periods of global crisis significantly disrupt creative industries, particularly the visual and performing arts, where artistic production is closely linked to institutional support, regulatory frameworks, and cultural policy. This paper examines creative industry regulation in times of crisis by drawing comparative lessons from COVID-19 enforcement measures and healthcare cartel policies implemented in India, Australia, and Singapore. Through an interdisciplinary policy analysis, the study explores how emergency regulatory responses—originally designed for essential sectors such as healthcare—offer valuable insights for governing creative and design-led industries during periods of uncertainty. The research contextualizes these regulatory approaches within the creative economy, emphasizing their implications for artistic labour, cultural organizations, and design-driven enterprises. By comparing national responses, the study identifies key governance themes including regulatory flexibility, collaborative compliance, and crisis-driven innovation. The paper argues that adaptive regulatory models can support continuity in creative production while safeguarding artistic autonomy. The findings contribute to emerging scholarship on cultural governance by proposing transferable policy lessons that strengthen resilience in visual and performing arts ecosystems. This research offers strategic insights for policymakers, cultural institutions, and creative practitioners seeking sustainable regulatory frameworks for future crises.